(Re) Making gender in the clinical context: a look at how ideologies shape the medical construction of gender dysphoria in Portugal - Hilario, Ana Patricia (2019)
The act of diagnosing gender dysphoria (GD), as in the act of diagnosing any other condition, is structured by socio-cultural, political and economic factors and is conducted by social actors. Drawing upon in-depth interviews with practitioners who work with trans people in Portugal, the study reveals the nuances and complexities surrounding the diagnostic attribution of GD and the ways in which the ideologies regarding gender shape this attribution. Practitioners’ accounts show a diversity not often acknowledged within sociological and transgender literature. We extend previous studies by demonstrating that practitioners who operate under a social model of gender are opening space for trans people to be treated as experts of their bodies and identities by accepting the existence of those who identify beyond gender binaries. While it might not be true for practitioners who can be positioned within a biological model, thus attributing an essentialist explanation of gender, we found evidence that practitioners who follow a social model are allowing room for the self-definition of gender identification. The study provides another lens for understanding the diagnostic attribution of GD by paying attention to the accounts of practitioners who work with trans people and reveals their openness towards a collaborative model of care.